In the Eye of the Beholder! Visual Representations and Perceptions of Reality (KULT_online, 2020)
The volume deals with the investigation of the concept of 'eyewitness' in art and visual culture since 1800. For this purpose, the concept is explained in an understandable way using interdisciplinary case studies. It analyzes how reality and perception manifest in artistic and non-artistic artifacts. The case studies presented in the volume suggest that the perspective of the producer of the image, the viewer, and the visual representation are significant for the construction of reality.